Fairy tail. 25 - Mashima, Hiro, 1977- (Kodansha Comics, 2013)
"Natsu, Levy, Gray and the others face a fierce trial to reach the coveted S class! But with a mysterious death wizard wandering the island in search of Natsu, a mystery man manipulating the memories of the entire guild and a powerful dark force preparing to mount an invasion, one thing is clear-- this test really needs a proctor!" -- p. [4] of cover.